Securing VoIP and PSTN from integrated signaling network vulnerabilities - Sengar, Hemant; Ram Dantu; Wijesekera, Duminda (1st IEEE Workshop on VoIP Management and Security, 2006., 2006)
The liberalization of public switched telephone network (PSTN) and growing acceptance of SIGTRAN protocol suite have introduced new and yet to be trusted signaling entities. Thus security threats emerging from one network not only affects itself but other network also. We show how this integrated signaling environment can become a security threat to emerging VoIP and PSTN networks. We propose a security solution as a fix. Our proposal goes beyond "Gateway Screening" and "SS7 Gatekeeper" proposed by Telcordia and Verizon respectively to defend vulnerable SS7 network.
Keywords: Information security; Information systems; Internet telephony; IP networks; ISDN; National security; Protocols; Routing; Signal processing; Switching circuits